The Influence of Service Quality on Customer Satisfaction (Case Study of Outpatients of a Moslem Friendly Hospital in Gresik) - Alisyah Azzahra Putri; Rachma Rizqina Mardhotillah (Journal of Halal Research, Policy, and Industry, 2023)
Hospitals are one of the health service providers that have an important task to provide the best health service to the community. Hospitals have the tasks of medical care, health recovery, maintenance and improvement of individual health, organizing personal education and research and development of health technology. This study aims to analyze the effect of service quality on customer satisfaction. The research method uses quantitative methods with non-probablility sampling techniques with 170 respondents. The analysis in this study uses IPA (Importance Performance Anlysis) and CSI (Customer Satisfaction Index). IPA research results, there are 2 attributes in quadrant I, 13 attributes in quadrant II, 7 atributes in quadrant III, 3 attributes in quadrant IV. CSI research calculation obtained results of 88.8%